Zinc deficiency and cellular oxidative stress: prognostic implications in cardiovascular diseases - CHOI Sangyong; LIU Xian; PAN Zui (Acta Pharmacologica Sinica, 2018)
Zinc is an essential nutrient for human health and has anti-oxidative stress and anti-inflammatory functions. The association between zinc deficiency and the development of cardiovascular diseases (CVDs) has been supported by numerous studies. Supplementing zinc can reduce the risk of atherosclerosis and protect against myocardial infarction and ischemia/reperfusion injury. In this review we summarize the evidence in the literature, to consolidate the current knowledge on the dysregulation of zinc homeostasis in CVDs, and to explore the significant roles of the zinc homeostasis-regulatory proteins in cardiac physiology and pathophysiology. Moreover, this review also deliberates on the potential diagnostic and prognostic implications of zinc/zinc homeostasis-associated molecules (ZIP, ZnT, and MTs) in CVDs.